Character Education Values in the Jolat Jalit Dance - Mutiara Difa Fauziyah; Tati Narawati; Saian Badaruddin (Universitas Pendidikan Indonesia, 2025)
Describe the values contained in the Jolat Jalit dance and the process of learning the Jolat Jalit dance at the Swastika Art Studio in instilling character education and the form of instilling character education in children aged 7-12 years through Jolat Jalit dance learning activities. This study uses a qualitative methodology that is reviewed descriptively, with the object of research being the learning of the Jolat Jalit dance at the Swastika Art Studio, the participants of this study include the Jolat Jalit dance arranger and trainer and students of the Swastika Art Studio aged 7-12 years. Data collection techniques through observation, interviews, and documentation. Data analysis techniques in the form of qualitative descriptive through the stages of data reduction, data presentation, and drawing conclusions. The findings of the study indicate that the Jolat Jalit dance can be a medium for instilling character education values for children. The implementation of these values is carried out through routine practice, appreciation of the meaning of the movements, and instilling a positive attitude in every dance activity, there are aspects of religious, social, and moral values that the three values are contained in the Jolat Jalit dance which are contained in the values of religious character education, tolerance, discipline, hard work, creativity, independence, curiosity, love of the homeland, respect for achievement, communicative, love of peace, social care, and responsibility where these values are implemented through the learning process at the Swastika Art Studio to strengthen children's character and to provide knowledge that learning dance in the studio can also be a medium for character building for children, and knowing how to apply good learning in the art studio.